Numerical Investigation of Reinforced Soil Structures with GRS-IBS Design Features. Issue 6 (18th August 2020) - Gebremariam, F.; Tanyu, B.F.; Güler, E.; Urgessa, G.S.; Shen, P.
Abstract : This paper focuses on investigation of the effects of the presence of bearing bed and reinforced soil foundation (RSF), the vertical reinforcement spacing and reinforcement stiffness, and subgrade compressibility on design components including; the lateral displacement of facing, maximum tension in reinforcement (Tmax ), connection strength (To ), and differential settlement in reinforced soil structures reinforced with woven geotextile. The investigation was conducted through numerical simulation of reinforced soil structures using the finite element program, Plaxis 2D under plain strain condition. The results from the numerical analyses showed that the vertical reinforcement spacing has more effect on the design components than the reinforcement stiffness. The effect of slab load in widely spaced structures showed that the Tmax decreased with depth linearly. However, for the closely spaced structures with bearing bed, the reduction in Tmax with depth was bilinear. The existence of To in closely spaced structures was evident. The observed values of To were very close to values of Tmax . Inclusions of the bearing bed and RSF were found to have beneficial effects and can be implemented in design and construction of widely spaced reinforced soil structures to improve the performance.